Pengaruh Brand Image, Produk, dan Promosi terhadap Keputusan Pembelian Anggota Koperasi Kelurahan Merah Putih Candiroto Kecamatan Kendal Kabupaten Kendal - Sulaiman Kurdi; Muhammad Fauzi; Umi hani (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the effect of brand image, product, and promotion on purchasing decisions among members of the Merah Putih Village Cooperative in Candiroto, Kendal District, Kendal Regency. The research uses a quantitative associative approach with a sample of members from the Merah Putih Village Cooperative in Candiroto, Kendal. The sampling method used is saturated sampling, with a total of 127 respondents. The independent variables in this study are brand image, product, and promotion, while the dependent variable is purchasing decisions among cooperative members. Data analysis in this study involves instrument testing, classical assumption testing, and hypothesis testing using multiple regression with SPSS. The results show that, partially, brand image does not have a significant effect on purchasing decisions. This is evidenced by the t-count value of 0.758, which is greater than the t-table value of 0.1743, and the significance value of 0.450, which is greater than the significance level of 0.05. Product, in turn, does not significantly affect purchasing decisions with a t-count value of -1.708, which is smaller than the t-table value of 0.1743, and a significance value of 0.090, which is greater than the significance level of 0.05. However, promotion has a positive and significant effect on purchasing decisions. This is shown by a t-count value of 10.616, which is greater than the t-table value of 0.1743, and a significance value of 0.000, which is smaller than the significance level of 0.05. Simultaneously, brand image, product, and promotion have a positive and significant effect on purchasing decisions, with an F value of 40.432, which is larger than the F-table value of 0.1743, and a significance value of 0.000, which is smaller than the significance level of 0.05. The results indicate that promotion is the most influential factor in the purchasing decisions of cooperative members.